Sticky information and price controls: Evidence from a natural experiment - Doron Sayag; Avichai Snir; Daniel Levy (Economics Letters, 2025)
We test the predictions of the sticky information model using a survey dataset by comparing shoppers' accuracy in recalling the prices of regulated and comparable unregulated products. Because regulated product prices are capped, they are sold more than comparable unregulated products, while their prices change less frequently and vary less across stores and between brands, than the prices of comparable unregulated products. Therefore, shoppers would be expected to recall the regulated product prices more accurately. However, we find that shoppers are better at recalling the prices of unregulated products, in line with the sticky information model which predicts that shoppers will be more attentive to prices that change more frequently.
Keywords: D12; D83; D91; E31; K20; L11; L16; L50; 330; Sticky Information; Price Cap; Price Regulation; Price Control; Price Adjustment; Sticky Prices; Rigid Prices; Costs and Benefits of Information; Asymmetric Information